Body Language - Susan Quilliam
How to use the body's secret signals. First impressions do count and the body is the best tool for making a good and accurate initial impression. Knowing how to read body language reveals crucial mental attitudes and emotional tactics. Body Language is a practical guide to using the body to achieve greater professional and social success. Using jargon-free text and color illustration, the book explains how to quickly and correctly read a wide variety of body signals, how to express yourself better, how to respond more sensitively and how to improve relationships. After first impressions and territorial behavior, the book covers the body language used in personal and public situations Body Language has an impact on a wide variety of behavior, such as how to tell whether people are finding a joke funny, how to tell who is unattached and who is not, coping with authority and identifying dishonest behavior at work. Body Language includes an easy-to-read visual dictionary that shows key gestures with their meanings and reveals the contradictions that can occur between words and actions. The book takes a common sense approach to body language. While crossed arms are a clear indication of a closed mind, they can also indicate that the person is merely trying to stay warm. Body Language is a fascinating book about the most powerful and effective communication device, the human body.